Wood Science for Conservation of Cultural Heritage - Florence 2007 Proceedings of the International Conference held by COST Action IE0601 in Florence (Italy), 8-10 November 2007 - Luca Uzielli (Proceedings e report, 2009)
COST Action IE0601 "Wood Science for Conservation of Cultural Heritage" (www.woodculther.org) aims to improve the conservation (including study, preventive conservation and restoration) of European Wooden Cultural Heritage Objects (WCHOs), by fostering targeted research and multidisciplinary interaction between Researchers in various fields of Wood Science, Conservators of wooden artworks, other Scientists from related fields. This book of Proceedings contains most of the papers presented in the International Conference held in Florence (Italy) on 8-10 November 2007, dealing with several of the Action's themes, including structure and properties of historic wood, ageing and non-biological degradation of wood material, contributions from Wood Science to conservation issues.